Fabricating Ultra-thin Silicon Nitride Membranes Suspended on Silicon Wafer - Thi Hong, Pham; Huu Tung, Dang; Hai Anh, Nguyen; Tuan Linh, Dang; Thi Thu Thao, Nguyen; Thuy Hien, Dinh; Minh Hieu, Nguyen; Minh Hue, Nguyen; Tran Thuat, Nguyen; Viet Tuyen, Nguyen; Quoc Hung, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 37 No 1, 2021)
Ultrathin silicon nitride SiNx membrane suspended on a silicon wafer is a popular two-dimensional platform in MEMS applications. The unsupported membrane has a low thermal conductivity, is electrically insulated, and very robust against mechanical impact. Remarkably thin, it is difficult to fabricate and manipulate. Recently equipped with a dual chamber system for plasma enhanced chemical vapor deposition (PECVD) and reactive ion etching, we calibrate it to deposit silicon nitride Si3N4, silicon dioxide SiO2, and to dry etch these materials. Based on the superb quality of Si3N4, we perform a through-wafer etch that creates suspended Si3N4 membranes. The recipe is reliable and reproducible. We analyze the membrane’s chemical composition and optical properties. Although created by PECVD, the membrane is so robust that it survives multiple lithography steps. It extends our capability to study thermal transport at the submicron scale as well as to fabricate micron size devices for MEMS applicati